H5P como herramienta digital para la Enseñanza y Aprendizaje de Genética y Embriología con los estudiantes de séptimo semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología. - Miranda Escudero, Lisbet Tatiana (2025)
Technological innovation in education is essential to improve teaching and learning, as it allows educators to create dynamic and interactive scenarios. However, the problem arose from the lack of knowledge of new alternatives for digital tools in the Pedagogy of Experimental Sciences Chemistry and Biology course, which limits teachers and causes the use of unconventional methods that demotivate students. This research aims to propose interactive activities using H5P as a digital teaching tool for the study of Genetics and Embryology. The approach is quantitative, non-experimental in design descriptive, field, and bibliographical. The data collection and analysis were implemented using the survey technique, which was applied to 15 students legally enrolled in the seventh semester of the course. The results showed that the H5P teaching guide was positively valued, awakening interest in the subject and establishing a link between technology and content. It is concluded that H5P is a novel software that has the potential to enrich learning in an active and participatory way. The use of interactive resources from H5P in other subjects is recommended to further promote student engagement.